2003
DOI: 10.1017/s0031182003003780
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic characterization of the Fennoscandian cervid strain, a new genotypic group (G10) ofEchinococcus granulosus

Abstract: The northern biotype of Echinococcus granulosus occurs in North America and northern Eurasia in life-cycles involving cervids. Previously, cervid isolates of E. granulosus from North America have been characterized using molecular genetic techniques as the G8 genotype. In this study, 5 isolates of E. granulosus were collected from 4 reindeer and 1 moose in north-eastern Finland. DNA sequences within regions of mitochondrial cytochrome c oxidase I (COI) and NADH dehydrogenase I (NI)I) genes and the internal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(182 citation statements)
references
References 18 publications
7
174
0
1
Order By: Relevance
“…These informal groupings were retained for many years but with the advent of molecular characterization they were shown to be genetically distinct (Thompson and McManus, 2001). PCR-based techniques using a variety of genetic loci, and sequencing of nuclear and mitochondrial DNA, coupled with molecular epidemiological studies in endemic areas, confirmed the genetic and morphological distinctness of the host-adapted strains and revealed phylogenetic relationships which support a robust, meaningful taxonomy based on a previously documented nomenclature (Table 2; Bowles et al, 1994;Cruz-Reyes et al, 2007;Harandi et al, 2002;Huttner et al, 2009;Jenkins et al, 2005Lavikainen et al, 2003Moks et al, 2008;Nakao et al, 2013;Pednekar et al, 2009;Romig et al, 2006Romig et al, , 2015Saarma et al, 2009;Thompson et al, 1995Thompson et al, , 2006Thompson, 2001Thompson, , 2008Thompson and McManus, 2002;Tigre et al, 2016). Interestingly, the nomenclature used for these 'species' conforms to that proposed by observational parasitologists in the 1920se60s, before molecular tools were available to confirm and support their morphological descriptions and epidemiological observations Thompson and McManus, 2002;Thompson, 2008).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 64%
“…These informal groupings were retained for many years but with the advent of molecular characterization they were shown to be genetically distinct (Thompson and McManus, 2001). PCR-based techniques using a variety of genetic loci, and sequencing of nuclear and mitochondrial DNA, coupled with molecular epidemiological studies in endemic areas, confirmed the genetic and morphological distinctness of the host-adapted strains and revealed phylogenetic relationships which support a robust, meaningful taxonomy based on a previously documented nomenclature (Table 2; Bowles et al, 1994;Cruz-Reyes et al, 2007;Harandi et al, 2002;Huttner et al, 2009;Jenkins et al, 2005Lavikainen et al, 2003Moks et al, 2008;Nakao et al, 2013;Pednekar et al, 2009;Romig et al, 2006Romig et al, , 2015Saarma et al, 2009;Thompson et al, 1995Thompson et al, , 2006Thompson, 2001Thompson, , 2008Thompson and McManus, 2002;Tigre et al, 2016). Interestingly, the nomenclature used for these 'species' conforms to that proposed by observational parasitologists in the 1920se60s, before molecular tools were available to confirm and support their morphological descriptions and epidemiological observations Thompson and McManus, 2002;Thompson, 2008).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 64%
“…of vegetable contamined by eggs or by contact with a dog which may harbour different strains of E. granulosus (genotypes G1-sheep or G6-camel and further strains up to G10) described by Eckert & Thompson (1997) and Lavikainen et al (2003). Using multilocus enzyme electrophoresis in a previous study, we demonstrated that sheep, cattle and children are infested by the same common sheep strain strain in Tunisia (Oudni et al, 2004).…”
mentioning
confidence: 76%
“…Le et al, 2002;McManus et al, 2002;Obwaller et al, 2004;Lavikainen et al, 2003Lavikainen et al, , 2006Thompson et al, 2006;Nakao et al, 2007Nakao et al, , 2013bHüttner et al, 2008;Moks et al, 2008) and nuclear DNA sequences (e.g. Lavikainen et al, 2003;Bart et al, 2006;Saarma et al, 2009;Knapp et al, 2011).…”
Section: Phylogenetic Patternmentioning
confidence: 99%